Parámetros hematológicos en monos araña (ateles fusciceps) mantenidos en cautiverio en la fundación zoológico Santacruz. Cundinamarca, durante 2021-1. (2022)
The monkeys that belong to the Atelidae family are categorized as a critically endangered species (Cuarón et al. 2008). The International Union for the Conservancy of Nature indicates that the species family Atelidae (A, fusciceps) is is at critical risk. (Cuarón et al. 2008) (IUCN, 2020). It is necessary that in Colombia studies are carried out in which clinical constants can be parameterized for certain geographic regions, these data are quite useful during a clinical examination of monkeys that are in captivity and require medical attention or monkeys that arrive new to the Zoo facilities in order to provide better and prompt medical assistance